Combined Phialemonium curvatum and Acanthamoeba Keratitis: The Importance of Early Diagnosis and Specific Therapy. Issue 10 (October 2021) - Roszkowska, Anna M.; Severo, Alice A.; Biondo, Carmelo; Postorino, Elisa I.; Inferrera, Leandro; Aragona, Pasquale
Abstract : Purpose: To report the clinical and confocal findings of a unique case of combined Phialemonium curvatum and Acanthamoeba keratitis and to highlight the role of the prompt diagnosis and specific medical treatment in preserving visual function. Methods: A case report and literature review. Results: A 54-year-old woman presented with a 3-day history of visual impairment, photophobia, and ocular pain in her right eye. Her best corrected visual acuity was 0.4 Logarithm of the Minimum Angle of Resolution scale, and the slit-lamp examination showed whitish corneal stromal infiltrate with satellite lesions. In vivo confocal microscopy evidenced Acanthamoeba cysts and fungal hyphae that resulted P. curvatum in the culture examination. The intensive medical treatment was started with topical 0.02% polyhexamethylene biguanide, voriconazole 1%, and moxifloxacin hydrochloride 0.5%. Progressive improvement of clinical and confocal pictures was registered with a complete recovery of visual function after 1 month. Conclusions: This is the first case report of combined P. curvatum and Acanthamoeba keratitis. The fast diagnosis with in vivo confocal microscopy allowed early and intensive specific treatment with recovery of corneal infection.